Acid-Responsive Decomposable Nanomedicine Based on Zeolitic Imidazolate Frameworks for Near-Infrared Fluorescence Imaging/Chemotherapy Combined Tumor Theranostics - Guo, Heze; Mukwaya, Vincent; Wu, Daikun; Xiong, Shuhan; Dou, Hongjing (Pharmaceutics, 2024)
Zeolitic imidazolate framework-8 (ZIF-8) nanoparticles (NPs) are gaining traction in tumor theranostics for their effectiveness in encapsulating both imaging agents and therapeutic drugs. While typically, similar hydrophilic molecules are encapsulated in either pure aqueous or organic environments, few studies have explored co-encapsulation of chemotherapeutic drugs and imaging agents with varying hydrophilicity and, consequently, constructed multifunctional ZIF-8 composite NPs for acid-responsive, near-infrared fluorescence imaging/chemotherapy combined tumor theranostics. Here, we present a one-pot method for the synthesis of uniform Cy5.5&DOX@ZIF-8 nanoparticles in mixed solvents, efficiently achieving simultaneous encapsulation of hydrophilic doxorubicin (DOX) and hydrophobic Cyanine-5.5 (Cy5.5). Surface decoration with dextran (Dex) enhanced colloidal stability and biocompatibility. The method significantly facilitated co-loading of Cy5.5 dyes and DOX drugs, endowing the composite NPs with notable fluorescent imaging capabilities and pH-responsive chemotherapy capacities. In vivo near-infrared fluorescence (NIRF) imaging in A549 tumor-bearing mice demonstrated significant accumulation of Cy5.5 at tumor sites due to enhanced permeability and retention (EPR) effects, with fluorescence intensities approximately 48-fold higher than free Cy5.5. Enhanced therapeutic efficiency was observed in composite NPs compared to free DOX, validating tumor-targeted capability. These findings suggest ZIF-8-based nanomedicines as promising platforms for multifunctional tumor theranostics